Impact of exercise on psychological burden in adult survivors of childhood cancer: A report from the Childhood Cancer Survivor Study. Issue 17 (8th May 2019) - Tonorezos, Emily S.; Ford, Jennifer S.; Wang, Linwei; Ness, Kirsten K.; Yasui, Yutaka; Leisenring, Wendy; Sklar, Charles A.; Robison, Leslie L.; Oeffinger, Kevin C.; Nathan, Paul C.; Armstrong, Gregory T.; Krull, Kevin; et al.
Abstract : Background: Childhood cancer survivors are at risk for adverse psychological outcomes. Whether exercise can attenuate this risk is unknown. Methods: In total, 6199 participants in the Childhood Cancer Survivor Study (median age, 34.3 years [range, 22.0‐54.0 years]; median age at diagnosis, 10.0 years [range, 0‐21.0 years]) completed a questionnaire assessing vigorous exercise and medical/psychological conditions. Outcomes were evaluated a median of 7.8 years (range, 0.1‐10.0 years) later and were defined as: symptom level above the 90th percentile of population norms for depression, anxiety, or somatization on the Brief Symptom Inventory‐18; cancer‐related pain; cognitive impairment using a validated self‐report neurocognitive questionnaire; or poor health‐related quality of life. Log‐binomial regression estimated associations between exercise (metabolic equivalent [MET]‐hours per week −1 ) and outcomes adjusting for cancer diagnosis, treatment, demographics, and baseline conditions. Results: The prevalence of depression at follow‐up was 11.4% (95% CI, 10.6%‐12.3%), anxiety 7.4% (95% CI, 6.7%‐8.2%) and somatization 13.9% (95% CI, 13.0%‐14.9%). Vigorous exercise was associated with lower prevalence of depression and somatization. The adjusted prevalence ratio for depression was 0.87 (95% CI, 0.72‐1.05) for 3 to 6 MET hours per week −1, 0.76 (95% CI, 0.62‐0.94) for 9 to 12 MET‐hours per week −1, and 0.74 (95% CI, 0.58‐0.95) for 15 to 21 MET‐hours per week −1 . Compared with 0 MET hours per week −1, 15 to 21 MET‐hours per week −1 were associated with an adjusted prevalence ratio of 0.79 (95% CI, 0.62‐1.00) for somatization. Vigorous exercise also was associated with less impairment in the physical functioning, general health and vitality ( P trend < .001), emotional role limitations ( P trend = .02), and mental health ( P trend = .02) domains as well as higher cognitive function in the domains of task completion, organization, and working memory ( P < .05 for all), but not in the domain of cancer pain. Conclusions: Vigorous exercise is associated with less psychological burden and cognitive impairment in childhood cancer survivors. Abstract : In this report from the Childhood Cancer Survivor Study, vigorous exercise is associated with a lower risk of subsequent depression and somatization; even small amounts of vigorous exercise appear to be beneficial.